Human Resource Competencies and Their Influence on Time Performance in Construction Projects - siti asyiah; Mush'ab 'Abdu Asy Syahid; Tasya Rizqi Septyani Putri Hartoyo (Jurnal Teknik Sipil dan Perencanaan, 2026)
Human resource competencies play a crucial role in determining the success of construction projects, particularly in achieving project time performance. However, previous studies have predominantly focused on general performance indicators, with limited emphasis on the quantitative relationship between specific competency types and time performance in high-rise construction projects. This study aims to identify key human resource competencies and examine their influence on project time performance. A quantitative approach was employed, using questionnaire surveys and expert validation, and the data were analyzed using descriptive and nonparametric statistical methods. The findings reveal that 23 technical (hard skills) and 28 non-technical (soft skills) competencies are required. The most dominant hard skill is the understanding of structural work implementation, while the most influential soft skill is proactiveness and initiative. The results also indicate that technical competencies have a stronger relationship with time performance (60.7%) compared to non-technical competencies (56.8%). This study contributes by providing a structured quantitative assessment of competency-performance relationships, offering practical insights for improving workforce development strategies in construction projects.